The yeast centromere CDEI/Cpf1 complex: differences between in vitro binding and in vivo function. - Wilmen, A (1994)
The centromere and promoter factor Cpf1 binds centromere DNA element I found in all centromere DNAs from the yeast Saccharomyces cerevisiae. We analyzed thirty different point mutations in or around CEN6-CDEI (ATCACGTG) for their relative binding affinity to Cpf1 and these data were compared with the in vivo centromere function of these mutants. We show that the minimal length of the Cpf1 binding site needed for full in vitro binding and in vivo activity is 10 base pairs long comprised of CDEI plus the two base pairs 3' of this sequence. The palindromic core sequence CACGTG is most important for in vivo CEN function and in vitro Cpf1 binding. Symmetrical mutations in either halfsite of the core sequence affect in vitro Cpf1 binding and in vivo mitotic centromere function asymmetrically albeit to a different extent. Enlarging the CDEI palindrome to 12 or 20 bps increases in vitro Cpf1 binding but results in increased chromosome loss rates suggesting a need for asymmetrical Cpf1 binding sequences. Additionally, the ability of Cpf1 protein to bind a mutant CDEI element in vitro does not parallel the ability of that mutant to confer in vivo CEN activity. Our data indicate that the in vitro binding characteristics of Cpf1 to CDEI only partly overlap with their corresponding activity within the centromere complex, thus suggesting that in the in vivo situation the CDEI/Cpf1 complex might undergo interactions with other centromere DNA/protein complexes.